ECONOMY HAS TO BE IN ACCORDANCE WITH THE NEW SOCIETY? - Alexandru TRIFU; Loredana TEREC-VLAD (SEA: Practical Application of Science, 2016)

(untitled)
What we do not know yet regards the role of the economy in the post-human (future) society. Does the economy exist in such a society? We believe it does, and we also believe that the economy will not lose its status along with the transition from a society to another. Considering that in the post-human era the individual will live in a virtual space, there will be the so--called (human or non-human) workers who will take care of the maintenance of these virtual spaces. They will be types of economy, something like a hyper-technique, which is capable to interact with the economic and social mechanisms. At the same time, these new features are continuously supported by humans. The aim of this paper is to highlight the role of the economy within a future society. We will present aspects related to genetic engineering, trans-humanism and human enhancement in order to outline the fact that we cannot give up the economy.